Management of Oil Windfalls in Mexico : Historical Experience and Policy Options for the Future - Everhart, Stephen; Duval-Hernandez, Robert (World Bank, Washington, DC, 2014)
The macroeconomic impact of commodity windfalls has provided fertile ground for research since the 1970s. Particularly affected are developing countries that rely heavily on commodity exports. in the case of oil windfalls, cross-country experience is vast: Indonesia, Kazakhstan, Mexico, Nigeria, the Russian Federation, and Republica Bolivariana de Venezuela have all been buffered by such windfalls. The authors investigate Mexico's experience. They provide an overview of oil's impact on the Mexican economy and of the management of oil rents engineered by the government from the 1970s to date. A third of government revenues come from the hydrocarbon sector--especially oil exports. The reliance of public finance on a single commodity means that shocks threaten the economy's fiscal balance and stability. Policy options for protecting the economy from volatility in oil revenues without eliminating the benefits from rising prices include a stabilization fund and hedging strategies on international markets, which the authors discuss. The stabilization fund smoooths consumption and reduces the costs associated volatile spending. The fund and hedging strategies can complement each other--the fund working as the main recipient of revenues, and the hedging strategies managing short-lived movements in prices. This joint strategy would also reduce the size of the fund and the probability of its going bankrupt.